Regulating Income Tax: Case of Indonesian YouTubers - Prianto Budi Saptono; Cyntia Ayudia; Ismail Ismail Khozen (Fakultas Hukum Universitas Muhammadiyah Magelang, 2021)
Along with the development of digital business platforms in Indonesia, the YouTube content creator profession (YouTuber) has become a hard-to-tax sector due to the unavailability of a clear definition in the laws and regulations regarding the business characteristics of the content creator profession. This study aims to analyze the income tax aspect of content creators on the YouTube digital platform in Indonesia. First, it focuses on the interpretation of independent work and business activities related to the business nature of content creators, constituting individual taxpayers with income below the threshold regulated in Government Regulation (PP) no. 23 of 2018. Second, it analyzes the tax authority’s efforts and strategic measures to optimize tax revenues from YouTubers. This study uses a qualitative descriptive approach using documentation and literature studies. The results show that determining the income tax aspect of YouTubers requires carefulness in identifying the types of activities that become sources of income since they could either perform business activities or independent work simultaneously. Therefore, it is vital to confirm the YouTubers business activity definition in the tax provisions. In addition, adequate education and socialization that promote a cooperative approach become necessary to improve tax compliance.